Dynamics of political leadership and its impact on bureaucratic effectiveness - Noer, Hamka Hendra (International Journal of Innovative Research and Scientific Studies, 2025)
Political leadership is an important factor that can influence bureaucratic effectiveness. Strong and effective political leadership can encourage the bureaucracy to work better and achieve its goals. This research examines the factors that influence the dynamics of political leadership and their impact on bureaucratic effectiveness. This research uses qualitative methods, while the data collection technique is a literature study. The data that has been collected is then analyzed through three series, including data reduction, data presentation, and conclusion. The research results show that the factors that influence the dynamics of political leadership are changes in political regimes, political competition, and policy changes. Meanwhile, the impact on bureaucratic effectiveness is that it can bring in new and more competent political leaders, improving bureaucratic performance. Political competition can encourage political leaders to make various efforts to improve bureaucratic performance, and policy changes can encourage the bureaucracy to work more efficiently and effectively in accordance with new policies.